Penetapan Asal Usul Anak Akibat Perkawinan Siri dalam Ikatan Perkawinan yang Sah - Mohamad Hoirul Anam (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
This study aims to examine and analyze the legal status of children born from unregistered (siri) marriages from the perspective of Indonesian positive law and Islamic law. Although siri marriages are considered religiously valid, they lack formal legal force if not officially registered with the authorized state institution. Consequently, children born from such unions are not automatically recognized as legitimate under positive law, as stipulated in Law Number 1 of 1974 on Marriage. However, following the Constitutional Court Decision No. 46/PUU-VIII/2010, children born out of wedlock may be legally acknowledged to have a civil relationship with their biological father if proven scientifically (e.g., through DNA testing) and/or with other legally accepted evidence. In contrast, Islamic law holds that children born from marriages that fulfill the religious requirements though not administratively registered still have a legitimate lineage (nasab) and are entitled to legal protections such as maintenance and inheritance. This research uses a normative juridical approach with qualitative descriptive analysis of statutory regulations, court decisions, and scholarly opinions. The findings highlight the need for harmonization between Islamic law and national law, as well as enhanced legal protection for children born from siri marriages through regulatory strengthening and increased public awareness regarding marriage registration.